The Error in Drawing Graphic of Quadratic Function in PBL Model by Using True or False Strategy with GeoGebra-Assisted - Lukmanul Akhsani; Erlin Nurhayati (AlphaMath : Journal of Mathematics Education, 2020)
Quadratic function is one of the important topic in mathematics. The purpose of this study is to describe the mistakes made by students when drawing a quadratic function graph. In this research, the focus of the problem is what type of mistakes made by students in drawing a graph of quadratic functions. The form of error here referred to an error in doing the exercise of drawing quadratic function graph in learning with the PBL model using a true or false strategy assisted by GeoGebra application. The conclusion of this research states that the error in drawing quadratic function graph is dominated by procedural errors. PBL model with true or false strategy with the help of GeoGebra application can be an alternative learning to overcome students' mistakes in drawing quadratic function graphs